Reciclagem de poli (tereftalato de etileno) (PET) : aplicação tecnológica de etanol supercrítico catalisado por líquidos iônicos [Bmim][BF4] e [HMim][HSO4] - Nunes, Cátia Santos (2014)
Poly(ethylene terephthalate) (PET) is a thermoplastic with excellent properties such as mechanical and chemical resistance, thermal stability. Despite its good qualities, PET is not biodegradable and its negligent disposal has been resulting in serious environmental problems. According to this scenario, chemical recycling of PET is an alternative to this issue in order to reduce if not completely solve it. In the present Thesis the possibilities of using the ionic liquids [Bmim][BF4] and [HMim][HSO4] or the salt [TMA][BF4] combined to the particular characteristics of supercritical ethanol to perform the depolymerization of PET were evaluated by means the recovery and purification of the original monomers. For that, PET was depolymerized using ethanol above its critical conditions (temperature and pressure) taking into account the influence of other compounds such as water content and presence of dyes. The PET was successfully converted in diethyl terephthalate (DET) with a 98 and 96% in weight using [Bmim][BF4] and [HMim][HSO4] as catalysts, respectively. Using such catalysts allowed considerably reduction in the depolymerization time from 6 h to 45 min. However, water and dyes in the bulk (present in the composition of PET bottles) affect these depolymerization yields, acting as a poison in the catalyst decreasing the catalyst activity. The results showed that the yield decreases to 30% in DET when different amounts of water were added to the reaction medium and to 66% and 21% when 2-amino anthraquinone and zinc phthalocyanine present in colored (green and blue, respectively) PET bottles. When the salt [TMA][BF4] was used as catalyst instead ionic liquids, a yield of 75% in DET was obtained. In the presence of water the yield of salt catalyzed reaction decreased to less than 1.5%, and the presence of dyes (present on colored PET bottles) in the reaction environment did not affect the yield of PET depolymerization. With the intention to complete the recycling cycle, the monomer (DET) obtained from the depolymerization of PET (raw) under scEtOH condition was reused in the polymerization of poly (ethylene terephthalate)